Association between health anxiety dimensions and preventive behaviors during the COVID-19 pandemic among Japanese healthcare workers - Kentaro Nagao; Takuya Yoshiike; Ryo Okubo; Kentaro Matsui; Aoi Kawamura; Muneto Izuhara; Tomohiro Utsumi; Megumi Hazumi; Mio Shinozaki; Ayumi Tsuru; Yohei Sasaki; Kazuyoshi Takeda; et al. (Heliyon, 2023)
Objective: Health anxiety (HA), defined as excessive worry about having a serious medical condition, may affect preventive behaviors during the coronavirus disease 2019 (COVID-19) pandemic. We examined the distinct role of two dimensions of HA—perceived likelihood (probability dimension) and awfulness of illness (awfulness dimension)—in self-protection, as reflected in preventive behaviors during the pandemic. Methods: Participants comprised 657 healthcare workers. Data were collected between February 24 and 26, 2021. The Short Health Anxiety Inventory determined the HA dimensions. Adherence to the government's recommendations for COVID-19 preventive behaviors was self-rated. An independent association between each HA dimension and participants' adherence to the recommendations was examined using multivariable regression. Results: Within the analyzed sample of 560 subjects, severe HA was observed in 9.1 %. The more the participants felt awful, the less frequently they engaged in the recommended preventive behaviors (adjusted odds ratio = 0.993, 95 % confidence interval: 0.989, 0.998, p = 0.003) regardless of their profession, working position, psychological distress, sleep disturbance, and current physical diseases. However, the probability dimension was not associated with their preventive behaviors. Conclusion: The awfulness dimension of HA could be a more sensitive marker of preventive behaviors than the probability dimension. Paying particular attention to the awfulness dimension may help optimize self-protection strategies during the COVID-19 pandemic. A two-dimensional understanding of HA may be useful for the maintenance of the healthcare system and public health as well as healthcare workers’ own health.